Stable Nuclear Zero: The Vision and its Implications for Disarmament Policy - Lodgaard, Sverre (Routledge Global Security Studies, 2017)
This volume examines the conditions necessary for a stable nuclear-weapons-free world and the implications for nuclear disarmament policy. The Nuclear Non-Proliferation Treaty (NPT) is a road map to nuclear zero, but it is a rudimentary one and it says nothing about the kind of zero to aim for. Preferably, this would be a world where the inhibitions against reversal are strong enough to make it stably non-nuclear. What then are the requirements of stable zero? The literature on nuclear disarmament has paid little attention to this question. By and large, the focus has been on the next steps, and discussions tend to stop where the NPT stops: with the elimination of the weapons. This book seeks to fill a lacuna by examining the requirements of stable zero and their implications for the road map to that goal, starting from the vision to the present day. The volume highlights that a clear conception of the goal not only is important in itself, but can shed light on what kind of disarmament process to promote. This book will be of much interest to students of nuclear proliferation, global governance, security studies and IR. Introduction, Sverre Loodgaard and Satoko Takahashi PART I: A Nuclear Weapon Free World: Desirable? Feasible? 1. A world without nuclear weapons?, Thomas C. Schelling 2. Making NWFW Attractive, Stable and Sustainable, Manpreet Sethi 3. Icon Off the Mark, Harald Müller 4. Toward a Rigorous Comparison of a Pre-Nuclear and a Post-Nuclear World, Nikolai Sokov PART II: The Requirements and Paths to Stable Nuclear Zero 5. Out of the Box: Nuclear disarmament and Cultural Change, Harald Müller 6. Verification requirements, Andreas Persbo 7. Missile Defence as an Alternative to Nuclear Deterrence?, Tom Sauer 8. Nuclear Disarmament: A Chinese View, Jingdong Yuan 9. Stable at Zero: Deterrence and verification: Deterrence and Verification, Patricia Lewis PART III: Summary and Conclusions 10. The Vision and its Implications for Disarmament Policy, Sverre Lodgaard Sverre Lodgaard is Senior Research fellow and former Director of the Norwegian Institute of International Affairs (NUPI). He is author of Nuclear Disarmament and Non-Proliferation (Routledge, 2011) and co-editor of Nuclear Proliferation and International Security (with Bremer Maerli, Routledge, 2007).